Single-cell multi-omics for precision cardiovascular and longevity medicine: from methods to clinical translation - Osório, Thiago Guimarães; Pavesi, Estefania; El-Ardat, Khalil Abou; Qureshi, Needa; Cassidy, Leanne; St. John, Terrence Lee; Sirotin, Nicole; Piechowski-Jozwiak, Bartlomiej (Frontiers in Aging, 2025)
BackgroundSingle-cell multi-omics (SCMO) technologies simultaneously profile multiple molecular layers (e.g., DNA, RNA, proteins) within individual cells. Unlike traditional bulk analyses that average signals across thousands of cells, SCMO captures the unique molecular characteristics of each cell, potentially transforming our understanding of disease pathogenesis and clinical management. Despite its promise, SCMO methodologies remain complex and difficult for clinicians to interpret and utilize effectively.MethodsWe conducted a narrative review specifically tailored to clinicians, summarizing key SCMO methodologies, recent discoveries, and their translational relevance for cardiovascular and aging-related diseases. Our goal was to simplify complex SCMO concepts, highlight practical clinical insights, clarify methodological details in accessible terms, and openly discuss barriers currently preventing routine clinical implementation.ResultsSCMO techniques have identified clinically relevant cellular heterogeneity within diseases such as atherosclerosis and heart failure, uncovering subpopulations linked to disease severity and potential therapeutic targets. Notably, SCMO studies revealed specific inflammatory immune subsets in unstable plaques, pathogenic fibroblast populations driving cardiac fibrosis, and distinct immune profiles associated with aging and longevity. Early clinical trials integrating SCMO demonstrate feasibility in oncology and cardiology, and prototype clinical assays (e.g., single-cell “liquid biopsies”) are emerging. These advances are yielding predictive biomarkers and guiding personalized and preventive applications.ConclusionSCMO is rapidly evolving, offering unprecedented precision in diagnostics and personalized therapeutics by pinpointing disease-driving cells and molecular pathways. However, significant hurdles including high costs, technical complexity, and analytical challenges currently limit immediate clinical application. To the best of our knowledge, as of 2025, FDA authorization for single-cell diagnostics is limited to established technologies like flow cytometry, while next-generation multi-omic platforms remain confined to research use. This manuscript is explicitly designed to help clinicians navigate the complexity of SCMO, providing clear, digestible explanations of its methodologies and emphasizing how these tools might practically benefit patient care. Clinicians should remain cautiously optimistic, viewing SCMO as a complementary, specialized tool. Continued technological and methodological advances suggest SCMO will become increasingly integral to precision medicine.